Plague in Arab Maghreb, 1940–2015: A Review - Malek, Maliya Alia; Bitam, Idir; Drancourt, Michel (Frontiers in Public Health, 2016)
We reviewed the epidemiology of 49 plague outbreaks which resulted in about 7,612 cases in 30 localities in the Arabic Maghreb (Mauritania, Morocco, Algeria, Tunisia, Libya and Egypt) over 75 years. Between 1940 and 1950, most cases recorded in Morocco (75%) and Egypt (20%), resulted from plague imported to Mediterranean harbours and transmitted by rat ectoparasites. In contrast, the re-emergence of plague in the southern part of Western Sahara in 1953 and in northeast Libya in 1976, was traced to direct contact between nomadic populations and infected goats and camels in natural foci, including the consumption of contaminated meat, illustrating this neglected oral route of contamination. Further familial outbreaks were traced to human ectoparasite transmission. Efforts to identify the factors contributing to natural foci may guide where to focus the surveillance of sentinel animals in order to eradicate human plague, if not Y. pestis from the Arab Maghreb.